2006
DOI: 10.1097/01.wnr.0000209004.63352.10
|View full text |Cite
|
Sign up to set email alerts
|

Rapid visual stimulation induces N-methyl-D-aspartate receptor-dependent sensory long-term potentiation in the rat cortex

Abstract: Previously we have demonstrated that rapidly presented sensory stimulation (visual or auditory) can induce long-lasting increases in sensory evoked potentials recorded from the human cortex. Long-term potentiation was suggested as the underlying mechanism of these increases. In the present experiment, we applied the same visual paradigm to anesthetized rats to investigate the properties and mechanisms of this effect. Our results indicated that visual evoked responses were significantly enhanced for at least 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
83
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 22 publications
12
83
0
Order By: Relevance
“…This is consistent with prior findings that DCS augmented increases in motor cortex excitability following anodal transcranial direct-current stimulation in humans (37) and augmented LTP in rat hippocampus following high-frequency electrical stimulation (38,39). Our finding is also consistent with preclinical studies demonstrating that potentiation of the VEP following HFvS is NMDAR dependent (8).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with prior findings that DCS augmented increases in motor cortex excitability following anodal transcranial direct-current stimulation in humans (37) and augmented LTP in rat hippocampus following high-frequency electrical stimulation (38,39). Our finding is also consistent with preclinical studies demonstrating that potentiation of the VEP following HFvS is NMDAR dependent (8).…”
Section: Discussionsupporting
confidence: 82%
“…It persists into adulthood, is frequently NMDAR dependent, and has been observed at subcortical and sensory cortex synapses (1-6). Although classical LTP studies used high-frequency electrical stimulation to induce LTP, HFvS also induces lasting potentiation of neural responses (8)(9)(10)(11)(12)(13)(14), and potentiated neural responses following HFvS show cardinal features of synaptic LTP (7,8). In the current study, participants who received DCS showed greater potentiation of the VEP following HFvS compared with participants who received placebo.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The increased amplitude of the early latency current sink in layer IV of the barrel cortex also suggests that at least part of the potentiation in this system could be located at the thalamocortical synapse or at subcortical synapses. It should be noted here that, because SEP waveforms, particularly laterlatency components, are generated by the combined activity of several neuronal populations (Di et al, 1990;Jellema et al, 2004), waveform plasticity may reflect synaptic plasticity as well as plasticity occurring through other mechanisms, such as changes in neuronal excitability or in the activity of inhibitory interneurons ( Clapp et al, 2006). Interestingly, earlier studies showed that rhythmically patterned bursts of electrical stimulation in thalamic sensory relay nuclei, with frequencies of 5-7 Hz, could induce long-lasting potentiation of cortical responses to natural peripheral or single-pulse thalamic stimulation in the adult rat (Lee and Ebner, 1992;Heynen and Bear, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It might also be that this activity facilitates the generation of long-term adaptive changes in cortical function that underlie perception (Gilbert et al, 2001). Recent evidence suggests that periods of rhythmical visual or auditory stimulation can induce properties of synaptic plasticity such as long-term potentiation of cortical responses evoked by sensory inputs (Clapp et al, , 2006Teyler et al, 2005). Whether similar mechanisms could be related to whisking activity and whether such changes could be behaviorally relevant is not known.…”
Section: Introductionmentioning
confidence: 99%